Stakeholder perspectives on BIM-LCA integration in building design: Adoption, challenges, and future directions - Parece, S.; Resende, R.; Rato, V. (Building and Environment, 2025)
Europe's ambitious net-zero carbon targets compel the AEC sector to quickly adapt. Mandatory whole-life carbon declarations will require stakeholders to quantify and reduce environmental impacts using Life Cycle Assessment (LCA). However, LCA is widely perceived as complex, time-consuming, and costly. Building Information Modelling (BIM) has the potential to streamline LCA processes (e.g., quantity take-off). Research on BIM-LCA integration has grown substantially since 2013, but the extent of its adoption in practice remains unclear, as the perspectives of end-users have been largely overlooked. This study addresses this gap by assessing BIM-LCA adoption and end-user challenges through a mixed-methods approach: a survey of 62 stakeholders and a focus group with six LCA specialists. Results show that while 82% of participants apply sustainability strategies, only 45% have experience with LCA, and just 29% use BIM-LCA tools. LCA is most often conducted at late design stages, primarily to comply with certification requirements. Barriers reported include the lack of comprehensive environmental databases, limited interoperability, demanding information requirements, repetitive manual tasks (e.g., BoQ edition and mapping BIM and LCA data), lack of an interactive process (real-time feedback), and limited support for result interpretation. Participants expressed strong interest in early-stage parametric modelling, continuous performance monitoring, real-time BIM synchronisation, and integrated multi-criteria decision analysis and multi-objective optimisation. Beyond diagnosing challenges, this study identifies recent research developments addressing these issues and proposes priority actions for user-oriented BIM-LCA across four areas: Data & Standardisation, Automation & Digital Tools, Education & Skills, and Decision Support methods.